Исследование процесса равноканального Т-образного прессования методом конечных элементов - Спусканюк, Виктор Захарович; Гангало, Александр Николаевич; Давиденко, Александр Анатолиевич; Латаев, Александр Петрович (Eastern-European Journal of Enterprise Technologies, 2009)
The features of material flow and stress-strain state during the equal channel T-type pressing were investigated by finite element method. The influence of friction and material strain-hardening on billet shape, strain distribution and loading history during the pressing was shown.